Migraine - a borderland disease to epilepsy: near it but not of it - Paungarttner, Jakob; Quartana, Martina; Patti, Lucrezia; Sklenárová, Barbora; Farham, Fatemeh; Jiménez, Inés Hernando; Soylu, M Gokcen; Vlad, Irina Maria; Tasdelen, Semih; Mateu, Teresa; Marsico, Oreste; Reina, Federica; et al. (The journal of headache and pain, 2024)
BACKGROUND: Migraine and epilepsy are two paroxysmal chronic neurological disorders affecting a high number of individuals and being responsible for a high individual and socioeconomic burden. The link between these disorders has been of interest for decades and innovations concerning diagnosing and treatment enable new insights into their relationship. FINDINGS: Although appearing to be distinct at first glance, both diseases exhibit a noteworthy comorbidity, shared pathophysiological pathways, and significant overlaps in characteristics like clinical manifestation or prophylactic treatment. This review aims to explore the intricate relationship between these two conditions, shedding light on shared pathophysiological foundations, genetic interdependencies, common and distinct clinical features, clinically overlapping syndromes, and therapeutic similarities. There are several shared pathophysiological mechanisms, like CSD, the likely underlying cause of migraine aura, or neurotransmitters, mainly Glutamate and GABA, which represent important roles in triggering migraine attacks and seizures. The genetic interrelations between the two disorders can be observed by taking a closer look at the group of familial hemiplegic migraines, which are caused by mutations in genes like CACNA1A, ATP1A2, or SCN1A. The intricate relationship is further underlined by the high number of shared clinical features, which can be observed over the entire course of migraine attacks and epileptic seizures. While the variety of the clinical manifestation of an epileptic seizure is naturally higher than that of a migraine attack, a distinction can indeed be difficult in some cases, e.g. in occipital lobe epilepsy. Moreover, triggering factors like sleep deprivation or alcohol consumption play an important role in both diseases. In the period after the seizure or migraine attack, symptoms like speech difficulties, tiredness, and yawning occur. While the actual attack of the disease usually lasts for a limited time, research indicates that individuals suffering from migraine and/or epilepsy are highly affected in their daily life, especially regarding cognitive and social aspects, a burden that is even worsened using antiseizure medication. This medication allows us to reveal further connections, as certain antiepileptics are proven to have beneficial effects on the frequency and severity of migraine and have been used as a preventive drug for both diseases over many years. CONCLUSION: Migraine and epilepsy show a high number of similarities in their mechanisms and clinical presentation. A deeper understanding of the intricate relationship will positively advance patient-oriented research and clinical work.
Keywords: Migraine Disorders; Genetics; Migralepsy; migréna; komorbidita; lidé; Epilepsy; epilepsie; Comorbidity; Migraine with Aura; migréna s aurou; antikonvulziva; Migraine; Neurotransmitters; Hemiplegic migraine; Anti-seizure medication; Anticonvulsants; Humans